2017
DOI: 10.1111/jfpp.13300
|View full text |Cite
|
Sign up to set email alerts
|

Hot air drying and freeze drying pre-treatments coupled to explosion puffing drying in terms of quality attributes of mango, pitaya, and papaya fruit chips

Abstract: To further improve the quality of traditional combined hot air and explosion puffing drying (AD‐EPD) dehydrated tropical fruit, freeze drying, as a pre‐drying treatment, combined with explosion puffing drying (FD‐EPD) was applied to dry mango, pitaya, and papaya fruit. Comparative study of AD‐EPD and FD‐EPD in terms of physicochemical, texture, color, microstructure, and rehydration properties of the three tropical fruit chips was done. Compared with AD‐EPD, the crispness and the volume ration of the three tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
(62 reference statements)
2
24
0
2
Order By: Relevance
“…This is in consistent with the results of the study by Xiao et al ., who found that the DIC‐dried apple chips osmotically treated with different types of mono‐, di‐, and tri‐saccharide showed a similar hardness when SG was controlled at the same level. Crispness is an indicator of chewing, which is greatly related to the microstructure of crispy fruit and vegetable products . As expected, all of the osmotic pretreated samples exhibited higher crispness values (> 1.97 mm) than the un‐pretreated carrot chips (0.87 mm).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This is in consistent with the results of the study by Xiao et al ., who found that the DIC‐dried apple chips osmotically treated with different types of mono‐, di‐, and tri‐saccharide showed a similar hardness when SG was controlled at the same level. Crispness is an indicator of chewing, which is greatly related to the microstructure of crispy fruit and vegetable products . As expected, all of the osmotic pretreated samples exhibited higher crispness values (> 1.97 mm) than the un‐pretreated carrot chips (0.87 mm).…”
Section: Resultssupporting
confidence: 69%
“…Crispness is an indicator of chewing, which is greatly related to the microstructure of crispy fruit and vegetable products. 31 As expected, all of the osmotic pretreated samples exhibited higher crispness values (> 1.97 mm) than the un-pretreated carrot chips (0.87 mm). All of the above results indicate that apple juice concentrate can be used as an osmotic solution to improve the textural properties, which plays the same role as sucrose and maltitol.…”
Section: Texturesupporting
confidence: 72%
“…At present, solar drying is gradually replaced by hot‐air drying, which is widely used in food production because of its short drying time, simplified operation, controllable conditions, easy implementation, low investment cost, and more hygienic characteristics than those of solar drying (Maurya, Gothandam, Ranjan, Shakya, & Pareek, ; Ren, Perussello, Zhang, Kerry, & Tiwari, ). However, there are several disadvantages and limitations of these thermal drying techniques, which often cause heat damage and affect the color, flavor, texture, and nutritional value of the product, resulting in degradation of the final dried product quality (Valadez‐Carmona et al., 2017; Yi, Lyu, Bi, Zhou, & Zhou, ). To overcome this problem, there is an urgent need to introduce superior and more sophisticated preservation techniques to obtain dehydrated foods with high quality.…”
Section: Introductionmentioning
confidence: 99%
“…For heat sensitive materials, it is desirable to process them under mild conditions, so vacuum freeze drying is preferred in recent years, because it can maintain a good shape of the final products. However, the energy consumption of vacuum freeze drying is high, and freeze‐dried food products have the characteristics of highly hygroscopic and lack in flavor, which limits the application of this drying technology in industrial production . In contrast, the hybrid drying process has advantages in terms of low energy consumption, high product quality and high drying efficiency compared to the conventional drying processes.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many studies have shown that DIC can change the texture properties of products and improve the quality of product. This drying technology has been successfully applied in processing of various fruit or vegetable materials such as apple, peach, mango, papaya, strawberry, jujube, and carrot . Most studies have focused on improving the quality of DIC dried products, including the adjustment of the operating parameters (such as puffing temperature, number of decompression, continuous vacuum time, and continuous vacuum temperature, etc.)…”
Section: Introductionmentioning
confidence: 99%